The Quality of Industrial Policy and Middle Income Traps: Comparing Vietnam with other Countries - Ohno, Kenichi (VNU Journal of Science: Social Sciences and Humanities, 2017)
This paper conducts a pilot research on the relationship between industrial policy quality and growth performance. A middle income trap is defined as a situation where the domestic economy is unable to create value beyond what is delivered by given advantages. Given advantages include natural, demographic and geographical factors as well as such external factors as trade, aid, and foreign investment inflow. When growth depends mainly on these factors, little domestic value is created and the economy does not reach high income. The private sector should be the main creator of value-added and economic growth, but it is generally recognized that the proper guiding role of government is equally important. The paper presents the hypothesis that the lack of industrial policy quality is the major cause of middle income traps among today’s emerging and developing economies. Vietnam’s industrial policy quality is compared with those of other nations in Asia and Africa. It is found that policy quality differs greatly across governments while the quality of different policy sub-components within the same government is quite similar. Industrial policy quality and per capita income are positively correlated, but there are groups of countries that exhibit high or low policy quality relative to their income. There is no clear evidence that natural resource endowment affects policy quality in either way. Vietnam’s policy score is near the bottom of the surveyed countries and Vietnam belongs to the group where policy quality is lower than what is expected from the income level. Improving industrial policy requires not just discussion of what needs to be done but, more importantly, a reform of policy methodology and invigoration of private dynamism with proper stimuli.